What are We Learning and What Can We Learn from the Human Oral Microbiome Project? - Cross, Benjamin (Curr Oral Health Rep, 2016)
Extraordinary technological advances have greatly accelerated our ability to identify bacteria, at the species level, present in clinical samples taken from the human mouth. In addition, technologies are evolving such that the oral samples can be analyzed for their protein and metabolic products. As a result, pictures are the advent of personalized dental medicine is becoming closer to reality.